Preparation of microfluidics device from PMMA for liposome synthesis - Van , Tran Thi Thanh; Huy Trung, Nguyen; Hong, Cao Thi; Thai, Vu Quoc; Dung, Trinh Quang; Duong, Nguyen Thanh (Vietnam Journal of Science and Technology, 2023)
Microfluidics has emerged in recent years as a technology that has advantages and is well suited for studying chemistry, biology, and physics at the microscale. A common material which has been widely use to fabricate the microfluidic system is thermoplastic materials. The method of fabricating microfluidic devices has been growing because of advantages such as high-quality feature replication, inexpensiveness, and ease of use. However, the major barrier to the utilization of thermoplastics is the lack of bonding methods for different plastic layers to close the microchannels. Therefore, this study focused on fabricating a microfluidic device on poly(methyl methacrylate) (PMMA) plates by laser engraving. The bonding technique for plastic layers has relied on the application of small amounts of ethanol with conditions of low temperatures (100 ⁰C), and relatively low pressures (5 tons) for 2 minutes. With this technique, the microfluidic device is created to operate stably, without leakage or cracking even under high pressure. The microfluidic device was applied to synthesize liposomes with a 5:1 ratio of syringe pump velocity between water and lipid solution. The size of liposomes after synthesis is 109.64 ± 4.62 nm (mean ± sd) and the PDI is in accordance with standard conditions (PDI < 0.200).